Mrs. Harris [videorecording (DVD)] - Nagy, Phyllis; Kingsley, Ben, 1943-; Bening, Annette (Home Box Office ; Distributed by Warner Home Video, 2006)
The Scarsdale diet doctor, famed cardiologist Herman Tarnower, meets a brutal end at the hands of his jilted lover, Jean Harris.